2018
DOI: 10.1007/s00253-017-8730-6
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum phosphoglucomutase is required for hyphal growth, polysaccharide production, and cell wall integrity

Abstract: Phosphoglucomutase (pgm) is an important enzyme in carbohydrate metabolism that is located at the branching point between glycolysis and the Leloir pathway. pgm catalyzes the reversible conversion reaction between glucose-6-phosphate (Glc-6-P) and glucose-1-phosphate (Glc-1-P). The glpgm gene was cloned in Escherichia coli, and the recombinant pgm protein from Ganoderma lucidum was purified in this study. The activity of native pgm was also detected to demonstrate that this predicted gene was functional in G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…lucidum were identified. Certain mitogen-activated protein kinases, transcription factor and phosphoglucomutases were found that could regulate hyphal growth, primordium formation or biosynthesis of chitin and polysaccharides through carbohydrate metabolic pathways [ 37 39 ]. Our results revealed more information about gene expression and protein abundance changes of the lignocellulolytic enzymes during G .…”
Section: Discussionmentioning
confidence: 99%
“…lucidum were identified. Certain mitogen-activated protein kinases, transcription factor and phosphoglucomutases were found that could regulate hyphal growth, primordium formation or biosynthesis of chitin and polysaccharides through carbohydrate metabolic pathways [ 37 39 ]. Our results revealed more information about gene expression and protein abundance changes of the lignocellulolytic enzymes during G .…”
Section: Discussionmentioning
confidence: 99%
“…About 2 mL of 95% ethanol was added to the filtrate, which was incubated at 4°C overnight after stirring vigorously. The sample was removed the next day, centrifuged, and dried; finally, 1 M NaOH was used to dissolve the precipitate and suspend the insoluble components at 60°C for 1 h. The phenol‐sulfuric acid method [24] was used to measure the EPS content. The collected mycelium was dried in an oven, and hyphae were collected for IPS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Hyphae (0.01 g) were weighed, suspended in 1 M NaOH, and placed at 60°C for 1 h. Then, the sample was centrifuged, and the supernatant was used to measure the IPS content. For the phenol–sulfuric acid method, glucose was used as a standard [24].…”
Section: Methodsmentioning
confidence: 99%
“…Medium A (g/L) (Tang and Zhong, 2002) contained glucose (35), tryptone (5), yeast extract (2.5), KH 2 PO 4 ⋅H 2 O (1), MgSO 4 ⋅7H 2 O (0.5), and Vitamin B 1 (0.05), with culture conditions of 30°C at 150 rpm. Medium B (g/L) (Hu et al, 2018) contained glucose (20), tryptone (2), yeast extract 2, KH 2 PO 4 (4.6), and MgSO 4 ⋅7H 2 O (0.5), with culture conditions of 30°C at 150 rpm.…”
Section: Methodsmentioning
confidence: 99%